Perbandingan Hasil Terjemahan Google Translate dan Microsoft Translator Pada Novel Mughamarah Zahrah Ma’a Asy-Syajarah Karya Ya’qub Asy-Syaruni - Zahroh, Heniatus; Basid, Abdul; Jumriyah, Jumriyah (Al-Lisan: Jurnal Bahasa, 2023)
This research aims to compare the translation results of Google Translate and Microsoft Translator based on grammatical aspects devoted to fi'il ma’lum-majhul, zaman al-fi'l, and dhamir. This type of study is qualitative, comparative, and descriptive. The main source of data in this research is the novel Mughamarah Zahrah Ma'a Ash-Shajarah by Yacoub Al-Sharouni. Secondary data sources are literature related to Arabic grammatical rules, google Translate translation, and Microsoft translator. The data collection technique is translating a novel by a sentence from Arabic to Indonesian using Google Translate and Microsoft Translator and then recording it. Data validation techniques are performed by triangulation of data and time. Data analysis techniques use data reduction techniques, data presentation, and conclusions. The result of this research is that Google Translate produces good translations in terms of fi'il ma'lum-majhul. Google Translate and Microsoft Translator are inconsistent in translating zaman al-fi'l, while Microsoft Translator produces good translations in terms of dhamir.